Importing care, faithful service Filipino and Indian American nurses at a veteran's hospital - Cherry, Stephen (Critical issues in health and medicine)
Every year thousands of foreign-born Filipino and Indian nurses immigrate to the United States. Despite being well trained and desperately needed, they enter the country at a time, not unlike the past, when the American social and political climate is once again increasingly unwelcoming to them as immigrants. Drawing on rich ethnographic and survey data, collected over a four-year period, this study explores the role Catholicism plays in shaping the professional and community lives of foreign-born Filipino and Indian American nurses in the face of these challenges, while working at a Veterans hospital. Their stories provide unique insights into the often-unseen roles race, religion and gender play in the daily lives of new immigrants employed in American healthcare. In many ways, these nurses find themselves foreign in more ways than just their nativity. Seeing nursing as a religious calling, they care for their patients, both at the hospital and in the wider community, with a sense of divine purpose but must also confront the cultural tensions and disconnects between how they were raised and trained in another country and the legal separation of church and state. How they cope with and engage these tensions and disconnects plays an important role in not only shaping how they see themselves as Catholic nurses but their place in the new American story.